Innovative Tourism Partnership Models: The Case of Nautical Stations in Portugal and Spain - Amaral, Marta (2020)
This chapter provides a deeper insight into the concept of a nautical station. More specifically, it tries to determine the importance of partnership models defined by digital platforms as a tool for a cooperation strategy in the development of new products; such is the case of nautical tourism in Portugal, a coastal nation in southwestern Europe. With this objective in mind and framed by the concept of the nautical station as a starting point, a descriptive analysis explores this topic. The case of Spain, with the development of the Nautical Resorts Association, is a model for best practice that must be not replicated but adapted to the situation in Portugal. This chapter advocates that nautical tourism, as a strategic tourist product for Portugal, will gain more prominence and strength if supported by a collaboration model between the various stakeholders of the tourism system framed by partnership models.